Effect of Orally Administrated Acriflavine to larval of Red Tilapia (Oreochromis sp.) on Their Sex Ratio - M. Zairin Junior; D. Nurlestiyoningrum; M. Raswin (Jurnal Akuakultur Indonesia)
Uncontrolled and excessive spawning of red tilapia (Oreochromis sp.) hinders fish growth to reach marketable size.  Several techniques have been developed to produce monosex population to overcome the problem, such as sex reversal by hormonal administration.  Androgen hormone is generally employed to meet the goal, although the use of this hormone had been restricted and its price is relatively high. Acriflavine is an alternative chemical and its effect on sex development toward male fish has been proved.  In this study, acriflavine at dose of 0, 15, 25 and 35 mg/kg feed were fed to 10-day-old larvae for 6 weeks.  Feeding of larvae by diet containing 17a-methyltestosterone (MT) at dose of 50 mg/kg was also observed as a comparison of acriflavin treatment.  The results indicated that feeding of larvae by diet containing acriflavine 25 mg/kg (78.3%) and 35 mg/kg (79.0%) produced significantly higher percentage of male fish compared to 15 mg/kg and control.  However, the result is still lower compared to that of MT treatment (99.2%).  Acriflavine treatment had no effect on survival of red tilapia and survival rate was similar among treatments, ranged from 91.7% to 95.0%.